A Historical Analysis of the Impact of Hegemonic Masculinities on Sexual Assault in the Lives of Ethnic Minority Women: Informing Nursing Interventions and Health Policy. (January 2021) - Ruiz, Ashley; Luebke, Jeneile; Hawkins, Maren; Klein, Kathryn; Mkandawire-Valhmu, Lucy
Abstract : Women's experiences of sexual assault are rooted in and informed by a history that nurses need to understand in order to provide meaningful and effective care. In this article, we present a comprehensive literature review guided by intersectionality theory to deepen our understanding of the historical role that hegemonic masculinity plays in shaping ethnic minority women's experiences of sexual assault. Final sources included were analyzed using thematic analysis. On the basis of our analyses, we identified 4 themes: social order hierarchies, "othering" dynamics, economic labor divisions, and negative media/mass communication depiction. Our findings contribute to our understanding of these important histories that speak to the trauma of sexual violence inflicted upon the bodies of ethnic minority women, which we can incorporate into nursing education curricula. Incorporating this knowledge would equip nurses and allied health professionals with the necessary knowledge and skills that would enable them to help patients navigate multiple systems of oppression as they engage in help seeking following a sexual assault experience. This knowledge also acknowledges rather than dismisses the historically acceptable use of sexual violence against ethnic minority women. In addition, acknowledging these histories enables us to move forward as a society in engaging in an urgently needed cultural shift to address the hegemonic masculinities that perpetuate violence against women in the United States.